Histogenesis of Definite Cortex in Adrenal Gland During Postnatal Development in Buffalo - Kumar, Vishnudeo (Indian Journal of Veterinary Anatomy, 2020)
The study included the adrenal gland of 29 buffaloes ranging from day old to one year of age. The adrenal cortexwas made up of definite and foetal cortex in the day old buffalo calf. The zona glomerulosa was observed in the subcapsular area and consisted of darkly stained cells with irregular nuclei and large number of sinusoidal capillaries. The cellular mass in this zone was arranged in clusters of columnar cells and had spherical or oval nuclei surrounded by a homogenous cytoplasm. The zona fasciculata was interposed between the zona glomerulosa and foetal cortex in the adrenal gland of one week old buffalo calf. The cells of this zone were arranged in single or double cords and were larger in size. No mitotic figures were seen in the zona fasciculata or at the junction of zona fasciculata and foetal cortex. The zona fasciculata was more organized with the progression of age and contained cells with foamy cytoplasm. The zona reticularis was first time observed below the zona fasciculata in the adrenal gland of one and half month old buffalo calves. The cells of this zone were smaller than the cells of zona fasciculata. These cells were having little cytoplasm with pyknotic and heterochromatic nuclei. However, this zone was not well organized even in the adrenal gland of one year old buffalo.